Effectiveness and acute toxicity of intensity-modulated radiotherapy versus three-dimensional conformal radiotherapy in pancreatic cancer: a systematic review and a meta-analysis - Chang, Chia-Na; Hsu, Wan-Ting; Li, Guilin (Therapeutic Radiology and Oncology, 2018)
Background: Intensity-modulated radiotherapy (IMRT) produces a concave dose distribution to reduce gastrointestinal (GI) toxicity in patients with pancreatic cancer. The aim of this study is to summarize the current evidence on the survival and organ toxicity of IMRT in comparison with three-dimensional conformal radiotherapy (3D-CRT). Method: A search was conducted in the PubMed and EMBASE databases to identify studies that reported survival and radiation toxicity of IMRT compared to 3D-CRT. The primary endpoint for comparison was 1-year overall survival (OS). Pooled effect estimates were calculated using fixed-effect or random-effect models for all-cause mortality, acute GI toxicity and hematologic (HEMA) toxicity. Results: The initial search yielded a total of 528 articles from PubMed and EMBASE. After inclusion and exclusion based on pre-defined criteria, eight studies with head-to-head comparisons between IMRT and 3D-CRT were included for final analysis. In meta-analysis, The IMRT group was associated with a reduced 1-year mortality [relative risk (RR) =0.92; 95% confidence interval (CI): 0.86–0.99, P=0.017] and 2-year mortality (RR =0.96; 95% CI: 0.94–0.99, P=0.001). The radiation-induced ≥ grade 3 GI toxicity rate was significantly lower in the IMRT group than in the 3D-CRT group (RR =0.69; 95% CI: 0.50–0.96, P=0.046), while the HEMA toxicity was comparable between IMRT and 3D-CRT groups (RR: 1.13, 95% CI: 0.89–1.44, P=0.716). Conclusions: Despite several methodological and sample size limitations, reports from the current literature suggest a moderate survival advantage and attenuated GI toxicity of IMRT as compared with 3D-CRT. HEMA toxicity were found no significant difference between IMRT and 3D-CRT.